Inovasi Untuk Orientasi Baru Otonomi Daerah - Ernawati ' (Universitas Riau, 2012)
The study describes innovationsgood government bureaucracy. Developing strategies and empowering bureaucracy is not aninstant process. Experience in Indonesia shows that settlement policy of government officialswith no holistic solution will generate new problems shackled. Developing strategies and empowergovernment officials to comrehend resourcesshall new organization learning process should besupported by a good learning system supported organic-adaptic structure. This process is carriedout continuously through the process of mutual learning among bureaucrats, civil society andthe market wholeheartedly with the seriousness of the bureaucracy to public service positions.